Computer Security - ESORICS 2023 28th European Symposium on Research in Computer Security, The Hague, The Netherlands, September 25-29, 2023, Proceedings, Part II - Tsudik, Gene.; Conti, Mauro; Liang, Kaitai; Smaragdakis, Georgios; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
The four-volume set LNCS 14344-14347 constitutes the refereed proceedings of the 28th European Symposium on Research in Computer Security, ESORICS 2023, which took place in The Hague, The Netherlands, during September 25-29, 2023. The 93 full papers presented in these proceedings were carefully reviewed and selected from 478 submissions. They were organized in topical sections as follows: Part I: Crypto. Part II: Network, web and internet; privacy; and remote. Part III: Attacks; blockchain; and miscellaneous. Part IV: Machine learning; software and systems security. .
Crypto -- Network, web and internet -- Privacy -- Remote -- Attacks -- Blockchain -- Miscellaneous -- Machine learning -- Software and systems security.
Keywords: Data protection; Cryptography; Data encryption (Computer science).; Computer networks -- Security measures; 9; Computer systems; Data and Information Security; Cryptology; Security Services; Mobile and Network Security; Computer Communication Networks; Computer System Implementation